Demographic Change and Regional Labour Markets - Michael Johannes Böhm; Terry Gregory; Pamela Qendrai; Christian Siegel (Institute of Labor Economics (IZA), 2020)
Like many other countries, Germany has experienced rapid population and workforce ageing, yet with substantial variation across regions. In this paper we first use this spatial variation between 1975 and 2014 to estimate quasi-causal supply effects of ageing on regional labour market outcomes, drawing on the identification strategy of Böhm and Siegel (2020). We find in our panel of German labour market regions that workforce mean age has considerable negative effects on the wage returns to age. We also obtain suggestive evidence that relative employment rates of older workers decline when mean age rises. A decomposition of the heterogeneous regional trends using our estimates shows that ageing of rural regions is mainly driven by supply (reflecting local population dynamics) whereas urban ageing is driven by demand (reflecting responses to economic conditions). We discuss the differential implications of these drivers for regional policy.
Keywords: J11; J31; R23; 330; ageing; demographic change; regional differences; wage returns to age